Pieces of the periphery: A glance into the cartography of Ibibio’s CP domain - Doherty, John-Patrick (Kansas Working Papers in Linguistics, 2016)
Developments in cartographic observations of clause structure in Generative syntax predict strong formal linguistic universals among the ordering of phrases at the clausal edge. This ordering is assumed to result from a predetermined hierarchy that is defined by Universal Grammar (UG), reflecting an innate biological capacity for language in humans (Rizzi, 1989, p. 66). Ibibio, a Niger-Congo language, features a rich left periphery whose components demonstrate this hierarchical ordering. Through the interaction of left peripheral phenomena such as Argument Focus, Partial wh- movement, Q markers, and complementizers, this ordering is revealed. If Ibibio’s phrasal ordering differs from Rizzi’s proposed structure in (1), then the universality of Rizzi’s left periphery would be compromised. In addition to the phrases that Rizzi (1997) finds through Italian, Ibibio’s grammar parameterizes the activation of an additional phrase. We will find that the underlying order of Ibibio’s phrases does hold up to the posited hierarchy, supporting Rizzi’s (1997) proposition of the ordering of the left periphery in UG. Here is a comparison of these two peripheral structures.